1998
DOI: 10.1210/en.139.5.2452
|View full text |Cite
|
Sign up to set email alerts
|

Function of Galanin in the Anterior Pituitary of Estrogen-Treated Fischer 344 Rats: Autocrine and Paracrine Regulation of Prolactin Secretion

Abstract: Estrogen is a robust stimulator of galanin synthesis and secretion in the anterior pituitary. Galanin is colocalized in lactotrophs in the estrogen-treated anterior pituitary, and its roles in lactotroph function are still being elucidated. In the present studies, we quantified the phenotypes of estrogen-treated Fischer 344 rat anterior pituitary cells expressing the galanin gene by dual in situ hybridization. The total population of galanin-positive pituitary cells increased from undetectable levels to 16% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 0 publications
2
25
0
Order By: Relevance
“…It has been suggested that several effects of estrogens on lactotrope function and proliferation are mediated by lactotrope-derived VIP and galanin (Wynik et al 1993, Cai et al 1998. Similarly, our studies suggest that CT inhibits PRL release and PRL gene transcription, and also attenuates thyrotropin-releasing hormone (TRH)-and suckling-induced PRL release and synthesis (Shah et al 1988, Judd et al 1990.…”
Section: Gct1-asct-absupporting
confidence: 77%
“…It has been suggested that several effects of estrogens on lactotrope function and proliferation are mediated by lactotrope-derived VIP and galanin (Wynik et al 1993, Cai et al 1998. Similarly, our studies suggest that CT inhibits PRL release and PRL gene transcription, and also attenuates thyrotropin-releasing hormone (TRH)-and suckling-induced PRL release and synthesis (Shah et al 1988, Judd et al 1990.…”
Section: Gct1-asct-absupporting
confidence: 77%
“…1, 10, 13) is consistent with the idea of cell-tocell interactions by means of gap junctions. Many kinds of bioactive proteins other than the classic types of hormones have been found in the pituitary gland with immunohistochemical methods; e.g., angiotensin II [5,13], PACAP [8] and galanin [4,12]. These peptides are attractive candidates for paracrine factors regulating hormone secretion.…”
Section: Discussionmentioning
confidence: 99%
“…As Fischer 344 (F344) rats are particularly sensitive to this action, this strain has been commonly used to study the mitogenic action of E at the pituitary. Different endocrine and autocrine/paracrine factors, such as disruption of the dopaminergic axis [4, 5], transforming growth factor (TGF) beta 1 [6], TGF-β3 [7], basic fibroblast growth factor [8], or galanin [9, 10], are known to be involved in the mediation of the E-proliferative effect on lactotropes. However, it is still not well understood how these mechanisms are coordinated to induce lactotrope hyperplasia and tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%